TOLERANSI TANAMAN JAGUNG (Zea masy.L) PADA TANAH YANG DIBERI SLUDGE PULP DAN TSP - Aking Rahmad; Sulhaswardi Sulhaswardi (DINAMIKA PERTANIAN, 2013)
A research on maize tolerance on soil given sludge pulp and TSP was carried out at the experimental farm Faculty of Agriculture Riau Islamic University Pekanbaru from April to July 2012. The objective of the research was to see the tolerance sludge pulp and TSP interaction as well as individual on maize growth. The randomized completely design with two factorial was used for the experiment. The first factor was application of sludge pulp, consisting of four treatment namely P0 (control), P1 (14 g/plot), P2 (28 g/plot), and P3 (42 g/plot).The second factor was application of TSP, consisting of four treatment namely K0 (control), K1 (14 g/plot), K2 (28 g/plot), and K3 (42 g/plot). The observed parameters were plant height (cm), total wide leave (cm), bloomy age (day), harvested age (day), cob length (cm), number of row per cob (row), and seed weight per cob (kg). Data resulted from observation were analyzed statically and continued BNJ Test at 5% confidence level. As a result, tolerance of maize on soil given sludge pulp and TSp interactionally and individually had an effect on seed weight with the best result was showed by P3K3 treatment with 47.50 g. While, the obervation on plant height, total wide leave, bloomy age, harvested age, cob length, and number of row per cob had no a significant effect, but maize still can tolerate at a dosage of 42 g/plot.